Sharīʿah-compliance ratings of the Islamic financial services industry: a quantitative approach - Muhammad Hanif (ISRA International Journal of Islamic Finance, 2018)
Purpose: This study aims to develop a Sharīʿah-compliance rating mechanism for the Islamic financial services industry (IFSI), with a special focus on banking. The banking sector is taken as the area of focus due to its leadership role in the volume of global Sharīʿah-compliant assets. Design/methodology/approach The objectives of the Islamic financial system (IFS) are selected as the basis for ratings. A range of performance indicators (leading to achievement of the objectives) is grouped into four broader categories and used in the study to allocate scores with a sum total of 100. Special considerations - including the amount of resources required in performing an activity, suitability of prevailing business conditions, the degree of compulsion/discretion in performing a task and linkage with the essence of the IFS were taken into account in the allocation of scores. Findings This study groups multiple performance measures into four categories, including portfolio construction (deposits mechanism, participatory and asset-based modes of financing), access to finance (service to the less-privileged and sector screening), reputation (disclosures and stakeholders' survey) and Sharīʿah governance (Sharīʿah supervision and controls, charitable operations, human resources, product development and organization). The Portfolio, Audit, Reputation and System (PARS) rating system is then developed. Practical implications A Sharīʿah-compliance rating system is helpful in measuring the progress towards goal achievement of the IFS and in gaining stakeholders' trust. It is also important for Sharīʿah boards and regulators in policy formulation, for management in addressing weaknesses and taking corrective measures and potentially for standard-setting bodies. Originality/value This study presents a comprehensive quantitative Sharīʿah-compliance rating mechanism, taking into consideration the objectives of the IFS - equitable distribution of wealth and financial stability, in addition to Sharīʿah-compliance in operations. Development of Sharīʿah-compliance quality ratings for Islamic banking is essential to gain customers' trust; the suggested methodology is thus a contribution to the literature on Islamic finance.
Keywords: 330; Islamic banking portfolio; Islamic financial services; Sharīʿah audit; Sharīʿah governance; Sharīʿah-compliance ratings